Direct Antioxidant Properties of Bilirubin and Biliverdin. Is there a Role for Biliverdin Reductase? - Jansen, Thomas (Frontiers Research Foundation, 2012)
Reactive oxygen species (ROS) and signaling events are involved in the pathogenesis of endothelial dysfunction and represent a major contribution to vascular regulation. Molecular signaling is highly dependent on ROS. But depending on the amount of ROS production it might have toxic or protective effects. Despite a large number of negative outcomes in large clinical trials (e.g., HOPE, HOPE-TOO), antioxidant molecules and agents are important players to influence the critical balance between production and elimination of reactive oxygen and nitrogen species. However, chronic systemic antioxidant therapy lacks clinical efficacy, probably by interfering with important physiological redox signaling pathways. Therefore, it may be a much more promising attempt to induce intrinsic antioxidant pathways in order to increase the antioxidants not systemically but at the place of oxidative stress and complications. Among others, heme oxygenase (HO) has been shown to be important for attenuating the overall production of ROS in a broad range of disease states through its ability to degrade heme and to produce carbon monoxide and biliverdin/bilirubin. With the present review we would like to highlight the important antioxidant role of the HO system and especially discuss the contribution of the biliverdin, bilirubin, and biliverdin reductase (BVR) to these beneficial effects. The BVR was reported to confer an antioxidant redox amplification cycle by which low, physiological bilirubin concentrations confer potent antioxidant protection via recycling of biliverdin from oxidized bilirubin by the BVR, linking this sink for oxidants to the NADPH pool. To date the existence and role of this antioxidant redox cycle is still under debate and we present and discuss the pros and cons as well as our own findings on this topic.